2021
DOI: 10.1080/23802359.2020.1870887
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the Chimaeridae taxonomy: the complete mitochondrial genome of the cartilaginous fish Hydrolagus mirabilis (Collett, 1904) (Holocephali: Chimaeridae)

Abstract: Cartilaginous fish are fascinating taxa, present in the folklore and art of many different cultures. Moreover, they display several unique anatomical, physiological, molecular, and behavioral characteristics making them extremely interesting from a biological perspective. Nevertheless, some crucial knowledge gaps remain, including phylogenetic relationships among extant species. Here, we produced the complete mitogenome sequence of the large-eyed rabbitfish, Hydrolagus mirabilis (Chimaeriformes). The complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Chimaeridae includes species traditionally placed in the genera Chimaera and Hydrolagus (Figure 2; Figure S3). However, as in previous studies we fail to resolve the reciprocal monophyly of these genera (Figure S3) [34,49,75,76]. Instead, we resolve four major clades in Chimaeridae, two of which necessitate the resurrection of available generic names.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Chimaeridae includes species traditionally placed in the genera Chimaera and Hydrolagus (Figure 2; Figure S3). However, as in previous studies we fail to resolve the reciprocal monophyly of these genera (Figure S3) [34,49,75,76]. Instead, we resolve four major clades in Chimaeridae, two of which necessitate the resurrection of available generic names.…”
Section: Resultsmentioning
confidence: 49%
“…We resurrect two genera, Bathyalopex and Phasmichthys, for clades in Chimaeridae that diverged from recognized lineages in the Jurassic and Cretaceous (Figure 2). This clarifies the systematics of living holocephalians, particularly confusion surrounding the classification of species traditionally placed in the chimaerid genera Chimaera and Hydrolagus [75,76]. Our placement of species in the genera †Ischyodus and †Elasmodectes on the stems of two lineages in crown Holocephali with strong nodal support across different analyses also provides a starting point for a reinterpretation of the fossil record of post-Paleozoic holocephalian fishes, which consists almost entirely of isolated tooth plates [83][84][85][86][87][88][89][90][91], on the basis of skeletal remains.…”
Section: Discussionmentioning
confidence: 55%
“…However, as previously observed (Gomes-dos-Santos et al. 2020 , 2021 ), neither Hydrolagus nor Chimera genera were recovered as monophyletic, which highlights the importance of revising the taxonomy. Indeed, previous authors had already suggested that the distinction between Chimera and Hydrolagus based on the presence or absence of a notch separating the anal from the caudal fin, respectively, needed revision (Didier et al.…”
mentioning
confidence: 54%
“… 2010 ), MW029477 ( H. mirabilis ) (Gomes-dos-Santos et al. 2021 ), HM147139 ( H. lemures ) (Inoue et al. 2010 ), KP006329 ( C. phantasma ) (unpublished), KP006330 ( R. africana ) (unpublished), HM147141 ( R. pacifica ) (Inoue et al.…”
Section: Resultsmentioning
confidence: 99%